2018
DOI: 10.1007/s11886-018-0968-9
|View full text |Cite
|
Sign up to set email alerts
|

Calcific Aortic Valve Disease: a Developmental Biology Perspective

Abstract: Purpose of ReviewThis review aims to highlight the past and more current literature related to the multifaceted pathogenic programs that contribute to calcific aortic valve disease (CAVD) with a focus on the contribution of developmental programs.Recent FindingsCalcification of the aortic valve is an active process characterized by calcific nodule formation on the aortic surface leading to a less supple and more stiffened cusp, thereby limiting movement and causing clinical stenosis. The mechanisms underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 176 publications
(144 reference statements)
0
47
0
Order By: Relevance
“…By combining a sophisticated approach to microdissect the regenerating tissues with transcriptomic analysis, we identified multiple genes potentially associated with early stages of valve regeneration, including the secreted TGFß ligand tgfß1b. Despite the fact that TGFß signaling deregulation in homeostasis induces pathological phenotypes in cardiac valves, such as ECM calcification (Anderton, et al, 2011;Wirrig and Yutzey, 2014;White, et al, 2015;Dutta and Lincoln, 2018), previous groups suggested that it may have a role in tissue regeneration, EndoMT and valve recellularization (Jazwinska, et al, 2007;Liu and Gotlieb, 2008;Benton, et al, 2009;Deng, et al, 2011;Li and Gotlieb, 2011;Chablais and Jazwinska, 2012). Using multiple genetic tools, we show that TGFß signaling is required at early regeneration stages and its enhancement promotes cell cycle re-entry and new valve cell differentiation.…”
Section: Identifying Molecular Regulators Of New Valve Cell Recruitmentmentioning
confidence: 63%
“…By combining a sophisticated approach to microdissect the regenerating tissues with transcriptomic analysis, we identified multiple genes potentially associated with early stages of valve regeneration, including the secreted TGFß ligand tgfß1b. Despite the fact that TGFß signaling deregulation in homeostasis induces pathological phenotypes in cardiac valves, such as ECM calcification (Anderton, et al, 2011;Wirrig and Yutzey, 2014;White, et al, 2015;Dutta and Lincoln, 2018), previous groups suggested that it may have a role in tissue regeneration, EndoMT and valve recellularization (Jazwinska, et al, 2007;Liu and Gotlieb, 2008;Benton, et al, 2009;Deng, et al, 2011;Li and Gotlieb, 2011;Chablais and Jazwinska, 2012). Using multiple genetic tools, we show that TGFß signaling is required at early regeneration stages and its enhancement promotes cell cycle re-entry and new valve cell differentiation.…”
Section: Identifying Molecular Regulators Of New Valve Cell Recruitmentmentioning
confidence: 63%
“…CAVD is a progressive disorder that ranges from mild valve thickening to severe formation of calcium phosphate nodules that impair leaflet movement (10). Formation of calcium nodules involves multiple factors, including endothelial dysfunction, inflammatory responses, as well as oxidative stresses on the valve that lead to valvular remodeling (15). Other risk factors for CAVD include hyperlipidemia, hypertension, chronic inflammation, and diabetes.…”
Section: Calcific Aortic Valve Disease (Cavd) and Atherosclerosismentioning
confidence: 99%
“…The underlying etiology of CAVD is largely unknown. While BAV is proven hereditary, there is limited information regarding genetic contributions to CAVD [reviewed in ( 8 )]. Risk factors are known and similar to most other cardiovascular diseases (hypertension, tobacco-use, hypercholesterolemia, etc.…”
Section: Introductionmentioning
confidence: 99%
“…), however the mechanisms that underlie calcific nodule formation on the aortic cusp surface following exposure to risk factors are largely unknown. The hemodynamic environment of the aortic valve is known to play a role in valve pathogenesis, and studies using animal and in vitro models have identified aberrations in critical signaling pathways required for valve formation in CAVD [reviewed in ( 8 )]. However, the field has yet to delineate cause and effect of these multifactorial contributors.…”
Section: Introductionmentioning
confidence: 99%